Weighted Composition Operators on the Zygmund Space - Shanli Ye; Qingxiao Hu (Abstract and Applied Analysis)
We characterize the boundedness and compactness of the weighted composition operator on the Zygmund space Z={f∈H(D):sup⁡z∈D(1-|z|2)|f″(z)|<∞} and the little Zygmund space Z0.